PENGARUH BUDAYA ORGANISASI TERHADAP HUBUNGAN ANTARA SISTEM INFORMASI AKUNTANSI MANAJEMEN DAN KINERJA MANAJERIAL (Studi pada Perguruan Tinggi Swasta di Kota Banda Aceh) - Syamsidar - (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2012)
This research is conducted at Private Universities in Banda Aceh and aimed at knowing the influence of the management accounting information system on the managerial performance as well as knowing that the organization culture strengthens the relationaship between the  management accounting information system  and the managerial performance at Private Universities in Banda Aceh. The respondents in this research include authorities at faculty and university levels at Private Universities in Banda Aceh. This research users 54 samples from a population of 116 people who are chosen through cluster random sampling. The data used are primary data which are collected through questionnaires distributed directly to the respondents. The technique of the data analysis used is multiple linear regression. The result of this research shows that the management accounting information system  has negative influence on the managerial performance at Private Universities in Banda Aceh. The organization culture strengthens the relationship between the accounting information system and the  managerial performance. Keywords: Management accounting information system,              organization culture and managerial performance